LOS PRINCIPIOS DE SIMPLIFICACIÓN, EFICACIA, CELERIDAD Y ECONOMÍA PROCESAL Y SU APLICACIÓN EN EL PROCEDIMIENTO ABREVIADO DE LA PERSONA PROCESADA - ENCALADA RAMÍREZ, MARÍA JOSÉ (2016)
This research is part of making a legal, analytical and critical study of "the principles of simplicity, efficiency, speed and procedural ECONOMY AND ITS APPLICATION IN SHORT PROCEDURE person prosecuted," and thus establish if in our country those principles apply to the Expedited Procedure and whether recidivism must be regarded as a way to toughen the penalty in these proceedings. It has developed a comprehensive theoretical framework related to determine clear and precise definitions of criminal offenses, prosecution, procedural subjects, the preliminary investigation stage, procedural stages, classes procedure, the simplified procedure in Ecuador and criminal regime. Once obtained and collected the basics has developed a study of the doctrinal trends mainly in relation to the origin of crime, types of crime, origin of summary procedure, origin of recidivism, the principles of simplicity, efficiency, speed and economy procedure, and then move to a study of the abbreviated procedure in other legislation as Argentina, Colombia and Chile. While it is true in most countries of the world including Ecuador has been given a special interest on the conduct of the offender or participant in this crime and determined criminal penalties for those who violate the law, our country has not been behind the criminality in our Comprehensive Organic Code of Criminal Procedure of those events that are produced by a person with will and 7 awareness and for their implementation produces damage there protected rights, but whose criminal behavior, can be resolved by alternative procedure as Abbreviated that agilitan processes and decongest the justice system; of the above, I must say that the Constitution of the Republic of Ecuador in Article 75 determines:. "... Everyone has the right to free access to justice and effective, impartial and expeditious protection of their rights and interests, subject to the principles of immediacy and speed; in no case it is defenseless. Failure of judgments will be punished by law ... •, indicating that and Ecuadorians are equal before the law, either as victims or as processed or accused of a criminal charge. But the fact remains that the Constitution of the Republic of Ecuador, said that the administration of justice emanates from the people and is based on the same principles in order to guarantee the rights of those involved in the criminal process and establishes: Article 167:. "... The power to administer justice emanates from the people and is exercised by the organs of the judiciary and other organs and functions established in the Constitution ..." Art. 169: "... EI procedural system is a means to the realization of justice. The procedural rules enshrine the principles of simplification, uniformity, effectiveness, immediacy, speed and procedural economy, and make effective the guarantees of due process. Justice shall not be sacrificed because of the omission of formalities ... alone. " 8 Ecuador is a constitutional state of rights and justice, and with the end of ensuring social order and people live in safety regulated by the law, therefore, all contrary to the same conduct is punishable when It is typical behavior, unlawful and culpable. It has made the presentation of the results of fieldwork, obtained from the application of the techniques of survey and interview, for the confrontation with the objectives and the hypothesis presented in the project, according to the results of the draw conclusions and recommendations that have come product of extensive and thorough analysis has been conducted in this investigation. Finally, after the field work performed developed legal proposal, a person who is a repeat offender the simplified procedure is applied but this when negotiating the penal between or the Prosecutor with the accused person is taken the maximum penalty for trading thereof, of which a third will be lowered. Within the thesis made have been analyzed various aspects differently with the simplified procedure and the preponderance which should give you inside the Ecuadorian penal system, mainly those features that distinguish it from ordinary procedure, such as agility when solving a crime and the need to invest scarce financial resources in order to have access to justice.